Uniform one-pot anchoring of Fe3O4 to defective reduced graphene oxide for enhanced lithium storage - Yoon, Dohyeon; Hwang, Jieun; Chang, Wonyoung; Kim, Jaehoon (ELSEVIER SCIENCE SA, 2017)
Highly uniform and tight anchoring of Fe3O4 nanoparticles on the surface of defective reduced graphene oxide (DRGO) is achieved using supercritical isopropanol (scIPA). The defect- and oxygen-rich sites of DRGO favor the heterogeneous nucleation and growth of Fe3O4 particles on its surface, while the unique reduction ability of scIPA helps remove some of the oxygen functionalities. The Fe3O4-DRGO composite exhibits a well-exfoliated mesoporous structure with a high specific surface area owing to the enhanced heterogeneous nucleation. When tested as an anode in Li-ion batteries, the Fe3O4-DRGO composite exhibits a high reversible discharge capacity of 1045 mAh g(-1) at a rate of 50 mAg(-1) and an excellent cycling capacity retention of 96% with almost 100% coulombic efficiency after 1000 cycles under a high charge discharge rate of 2.5 A g(-1). The comparison of physicochemical and electrochemical properties of Fe3O4-DRGO with those of the conventional Fe3O4-RGO composite revealed that the ultrafine Fe3O4 particle deposition, high surface area, and facile Li-ion transport to the active phase account for the high electrochemical performance of the Fe3O4-DRGO composite. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: LI-ION BATTERIES; HYDROGEN-CONTAINING CARBONS; ANODE MATERIAL; CYCLIC STABILITY; ENERGY-STORAGE; ELECTRODE MATERIALS; RATE PERFORMANCE; FE3O4-GRAPHENE NANOCOMPOSITES; ELECTROCHEMICAL PERFORMANCE; NANOSTRUCTURED MATERIALS